Exhumation Process in Oceanic and Continental Subduction Context: A Review - Guillot, Stéphane; Hattori, Keiko; Agard, Philippe; Schwartz, Stéphane; Vidal, Olivier (Université d'Ottawa | University of Ottawa, 2009)
Although the exhumation of high pressure (HP) and ultrahigh pressure (UHP) rocks is an integral process in subduction, it is a transient process, likely taking place during the perturbation in subduction zones. Exhumation of HP to UHP rocks requires the weakening of a subduction channel and the decoupling of the exhumed slice from the rest of the slab. Considering more than 60 occurrences of HP to UHP units of Phanerozic ages, we propose three major types of subduction zones: Accretionary-type subduction zones exhume HP metasedimentary rocks by underplating. The exhumation is slow and can be long-lasting. The serpentinite-type subduction zones exhume HP to UHP in a 1 to 10 km thick serpentinite subduction channel. The serpentinite matrix originates from both subducted abyssal peridotites and hydated mantle wedge. Exhumation velocity is low to intermediate and the exhumation is driven by the buoyancy and the low-viscosity of the serpentinite. The continental-type subductions exhume UHP rocks of continental origin. The UHP rocks together with garnet-bearing peridotites form units from km-scale unit. The exhumation is fast, short-lived and occurs at the transition from oceanic subduction to continental subduction. It is driven by buoyancy forces and asthenospheric return flow.
Keywords: Oceanic subduction; Continental subduction; Exhumation; HP to UHP rocks; Subduction channel